(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Shinkarenko V. Ethno-art culture as a component of professional competence of future teachers. In the article on the basis of comparison, comparison, synthesis of scientific information, it is proposed teaching learning process, based on folk traditions. Means and methods are disclosed of public education, with recommendations to the practical use of the results, to the competence of future teachers.